The art of preaching : a theological and practical primer - Cardó, Daniel (The Catholic University of America Press, 2021)
"The Art of Preaching: A Theological and Practical Primer explores the theological understanding of the homily, lessons from classical and contemporary rhetoric, the relevance of preaching for the life of the Church, highlighting recent teachings of the Magisterium, and it presents the incarnation as the foundation for preaching, understood as an essential aspect of the priestly life and mission. This primer offers a simple and effective method for the preparation and delivery of homilies. The book also provides a selection of homilies from the great preachers of the Church, organized chronologically, with brief introductions and commentaries that highlight what those homilies teach us for preaching today"--